PLAYING AND LEARNING: THE USE OF GAMES FOR THE DEVELOPMENT OF COGNITIVE SKILLS (CIPEEX, 2025)
Cognitive functions exert a direct influence on daily life, ranging from simple decisions to more complex processes, such as mathematical problem-solving. Childhood represents the stage of greatest cognitive and motor development, characterized by rapid brain growth and intense formation of neural connections, making the early stimulation of such abilities essential. This study aimed to report an extension activity conducted by nursing undergraduates, which employed cognitive games to stimulate logical reasoning and decision-making among 5th-grade elementary school students. The intervention took place on August 29, 2025, at Escola Municipal Dom Pedro I, in São Patrício, Goiás, involving children aged 9 to 11 years, organized into small groups and engaged in five games: pick-up sticks, checkers, battleship, dominoes, and Jenga. Students demonstrated interest, curiosity and engagement, although most reported never having played these games before. A preference for understanding the rules prior to gameplay was observed. However, only five students reported adopting planned strategies, while the majority exhibited impulsive or chance-dependent decision-making. It is concluded that there is a  lack of encouragement and access to games that promote cognitive skills, highlighting the need to expand pedagogical initiatives that promote rational and strategic decision-making during childhood. The limitation of the reduced sample size is acknowledged, and further studies with broader scope are recommended.
Keywords: childhood; logical reasoning; cognitive games